Evaluation of MADRS Severity Thresholds in Patients With Bipolar Depression. (April 2021) - Thase, Michael E.; Harrington, Amanda; Calabrese, Joseph; Montgomery, Stuart; Niu, Xiaomeng; Patel, Mehul
Abstract: Introduction: The Montgomery-Åsberg Depression Rating Scale (MADRS) is commonly used for the assessment of depressive symptom changes in patients with major depressive disorder (MDD) or bipolar depression. Categories of depression severity that correspond to ranges of MADRS total score have been previously reported in patients with MDD, but it appears that MADRS severity ranges have not been reported for patients with bipolar I disorder. The objective of this study was to evaluate MADRS total score ranges that correspond with different grades of depression severity in patients with bipolar I depression. Methods: Data were pooled from 3 randomized, double-blind, placebo-controlled, 6- or 8-week trials of cariprazine in patients with bipolar I depression. MADRS severity ranges were evaluated using an anchor-based approach with the clinician-rated, 7-category Clinical Global Impression-Severity (CGI-S) scale. CGI-S has previously been used to determine severity thresholds in MDD. Correlations between MADRS total score and CGI-S score were assessed in the pooled dataset at week 6; placebo and active treatment arms were pooled together. Youden index from receiver operating characteristic (ROC) curves was used to determine the optimal threshold for MADRS total score corresponding to each CGI-S severity level. Results: The pooled dataset included 1523 patients with bipolar depression. Mean CGI-S scores were highly correlated with mean MADRS total scores at week 6 (r=.87; P<.0001), with MADRS total scores increasing with CGI-S severity. Using the ROC curves, MADRS total score ranges corresponding to each CGI-S severity category were estimated as follows: score of 0-6 for "normal, not at all ill", 7-12 for "borderline mentally ill", 13-18 for "mildly ill", 19-23 for "moderately ill", 24-36 for "markedly ill", 37-39 for "severely ill", and 40 or greater for "extremely ill". Area under the curve (AUC) values for these cutoffs ranged from 0.930 to 0.997, representing outstanding sensitivity and specificity. Conclusions: Utilizing data from 3 recent clinical trials of subjects with bipolar depression, we were able to identify MADRS severity thresholds. These empirical findings may help clinicians to understand and contextualize MADRS results from bipolar clinical research and apply to their patients in practice. Funding: AbbVie Inc.